2008
DOI: 10.1097/sla.0b013e318176c4ec
|View full text |Cite
|
Sign up to set email alerts
|

Use of Recombinant Activated Factor VII in Patients Without Hemophilia

Abstract: Context: Benefits of recombinant activated factor VII (rFVIIa) in hemorrhage may be lost because of thromboembolic events (TAE). Method: MEDLINE, EMBASE, BIOSIS, CINAHL, Science Citation Index Expanded, clinicaltrials.gov were searched for placebo controlled trials of rFVIIa in patients without hemophilia. Reports of 22 randomized controlled trials were selected for analysis. Results were pooled using random effects models to calculate the odds ratios (OR) with 95% confidence interval (CI). Subgroup analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
1
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 44 publications
2
77
1
3
Order By: Relevance
“…12 The findings of our review are similar to those of a recent appraisal by Hsia and colleagues. 4 However, we grouped the RCTs by how recombinant factor VIIa was used (prophylactic or therapeutic), because the expectations of benefit and acceptance of risk in these two situations are different. This separation and greater attention to the risk of bias in the included stud ies has emphasized the degree of uncertainty about effectiveness of off-label use of recombinant factor VIIa.…”
Section: Discussionmentioning
confidence: 99%
“…12 The findings of our review are similar to those of a recent appraisal by Hsia and colleagues. 4 However, we grouped the RCTs by how recombinant factor VIIa was used (prophylactic or therapeutic), because the expectations of benefit and acceptance of risk in these two situations are different. This separation and greater attention to the risk of bias in the included stud ies has emphasized the degree of uncertainty about effectiveness of off-label use of recombinant factor VIIa.…”
Section: Discussionmentioning
confidence: 99%
“…2008 meta-analysis of 22 randomized controlled trials of rFVIIa in 3,184 patients without hemophilia showed that those receiving rFVIIa were less likely to require additional transfusions compared to those receiving placebo [22]. However, use of rFVIIa did not significantly decrease mortality nor did it increase the incidence of thromboembolic events.…”
Section: Meta-analysis and Systematic Reviewmentioning
confidence: 99%
“…A systematic review of RCTs, comparative and noncomparative cohort studies, retrospective cases series, and individual case reports of rFVIIa use in the setting of cardiovascular surgery also identified stroke to be the most common TAE with use of rFVIIa (2.6% of patients receiving rFVIIa experienced stroke, whereas 1.5% developed myocardial infarction, 0.8% had deep vein thrombosis, and 0.4% had intracardiac thrombosis). 41 Meta-analysis by Hsia and colleagues 42 of TAE rates across 22 clinical trials for various indications revealed a statistically significant increase in arterial thromboembolism (4.5% with rFVIIa vs 2.0% with placebo; P Ͻ .01).…”
Section: Rfviia Use In Spontaneous Ichmentioning
confidence: 99%